LAMENT PSALMS, THE CHRISTIAN COMMUNITY AND GOVERNANCE IN CONTEMPORARY NIGERIA - Uzoma Amos Dike (International Studies Journal)
Managing and coping with distress is one aspect of human life that remains a puzzle. Different cultures and traditions have developed means of handling issues of distress. Psalm scholars have discovered that in the lament psalms ancient Israel’s answer to the issues of life’s distress. By lament, the focus is on the category of psalms located within the worship setting that bemoan distressing situations of life and plead for divine intervention. Apart from mourning, several times the psalmists' lament comes inform of protest in the face of injustice, persecution, individual and communal disasters, among others. Governance in the Nigerian state has been plagued with a number of woes including insecurity and social injustice. Thus, the need to further explore justification for the Christian community in mobilizing lament to ease distresses ushered in by contemporary security challenges, create awareness for justice and foster national cohesion. This paper written from the functionalist perspective of religion, explored how the reading of lament psalms can initiate a healing process for the distressed Nigerian church and promote social cohesion. A multidisciplinary research approach was adopted premised on form criticism and conceptual review and sourced datawas critically analyzed. The paper discovered that communal reading of lament psalms in the face of national disaster provided sharing platforms where the distressed expressed pain by composing their distresses. Thus, the work maintains the efficacy of lament in initiating a healing process, strengthening communal bonds and eliciting the hope of restoration in the Nigerian situation.